(untitled) (Ius Novum, 2022)
The publication is devoted to the issue of adopting an adult. Under the Polish legislation in force, only a minor may be adopted. The study considers the legitimacy of introducing regulations allowing the adoption of adults to the family and guardianship code. It was pointed out that such solutions were in force in earlier Polish legislation. The proposals of the Human Rights Defender submitted in this respect were presented. In an attempt to support the legitimacy of the postulate to introduce into the Polish legal system legal norms allowing the possibility of adopting an adult, reference was also made to selected foreign legal systems guaranteeing this type of possibility.